Physicochemical Properties of Palm Oil Fraction (Elaeis guineensis Jacq) - Doloking, Haeria; Mukhriani, Mukhriani; Rusdi, Muh; Rafiâ€™ah, Silmi; Fitriana, Fadhilah (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2020)
Study about physicochemical properties of olein and stearin fraction of palm oil has been conducted. Research aim was to determine the chemical physical properties of the olein and stearin fractions of palm oil (Elaeis guineensi Jacq) that was originated from North Mamuju, West Sulawesi. Palm oil was fractionated by dry fractionation method to collect the olein and stearin fractions. The physical chemical characteristics of fractions were determined by acid value, saponification value, peroxide value, and iodine value parameters that measured by titrimetry method. The result of analysis showed that the acid values for the olein and stearin fractions acid were 7.04 and 5.83 mg NaOH/g, saponification values were 198.53 and 194.71 mg KOH/g, peroxide values were 0.77 mek O2/kg and 0.79 mek O2/kg, and iodine values were 34.12 and 32.87 g iod/100 g.